The Role of the Medan Immigration Detention Center in Handling the Problem of Rohingya Refugees in Medan City - Askhar Rizki Harahap; T. Riza Zarzani; Rahul Ardian Fikri (International Journal of Society and Law, 2024)
The ethnic Rohingya, a majority Muslim group living in the state of Rakhine, Myanmar, have been subjected to discrimination and violence forcing them to flee their country of origin. This crisis has led many Rohingya to seek refuge in neighbouring countries, including Indonesia. The city of Medan, as one of the metropolitan centers in North Sumatra, has become a shelter for Rohingya refugees. Immigration Detention Center (IDC) Medan, as a unit under the Immigration Directorate-General, plays a crucial role in dealing with these refugees. The study aims to find out the role of Immigration Detention Center (IDC) Medan in dealing with the Rohingya refugee problem and to analyze coordination and collaboration between Immigration Detention Center (IDC) Medan and the relevant parties. Using a qualitative approach, data is collected through in-depth interviews, participatory observations, and document analysis. The results of the research show that Immigration Detention Center (IDC) Medan is performs surveillance and administration in accordance with Presidential Regulation No. 125 of 2016. Immigration Detention Center (IDC) Medan is working intensively with various international organizations, government agencies, and non-governmental organizations to ensure effective and humane handling. This cooperation covers the relocation, protection, and provision of basic services to refugees. The study emphasizes the importance of coordination and collaboration to improve the effectiveness of the treatment of Rohingya refugees in the field. An integrated and collaborative approach is key to addressing challenges and providing adequate protection for refugees.